2018
DOI: 10.1111/jam.13720
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a laccase-coding gene from the lignin-degrading fungusPhlebia brevisporaBAFC 633 and heterologous expression inPichia pastoris

Abstract: The cis-acting elements may be involved in the transcriptional regulation of laccase gene expression. These results may provide a further insight into potential ways of optimizing fermentation process and also open new frontiers for engineering strong promoters for laccase production. The Lac I stability in chloride and solvents and broad decolorization of synthetic dyes are important for its use in organic synthesis work and degradation of dyes from textile effluents respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…Then, we can elucidate that more than six histidine tags at the amino region interfered with lac-case activity. Supporting our results, Fonseca et al (2018) obtained similar levels of recombinant laccase expressed in Pichia pastoris cloning with primers with a polyhistidine tag.…”
Section: Heterologous Expression Of Laccasesupporting
confidence: 84%
See 2 more Smart Citations
“…Then, we can elucidate that more than six histidine tags at the amino region interfered with lac-case activity. Supporting our results, Fonseca et al (2018) obtained similar levels of recombinant laccase expressed in Pichia pastoris cloning with primers with a polyhistidine tag.…”
Section: Heterologous Expression Of Laccasesupporting
confidence: 84%
“…For amplification and purification, 20 ng of DNA plasmid containing the coding region of the laccase gene, previously obtained by Fonseca et al (2018), was used. PCR amplifications were carried out using the cycling standardized by the working group (Fonseca et al, 2018). All fragments were separated by electrophoresis on 2% (w/v) agarose gel in 0.5× TBE buffer and stained with red gel.…”
Section: Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the selection of appropriate lignocellulosic biomass for fungus growth and enzyme production plays an important role in the development of efficient biotechnology (Elisashvili et al 2008;Han et al 2021a). There have been few studies on laccase related to the genus Phlebia, and previous studies were mainly focused on the effect of chemical and metallic compounds on laccase or the heterologous expression of a laccase gene (Kaneko et al 2009;Fonseca et al 2014Fonseca et al , 2018Janusz et al 2016). However, the effect of lignocellulosic biomass on laccase activity from the genus Phlebia has not been reported.…”
Section: Statistical Analysis Resultsmentioning
confidence: 99%
“…Gene was converted into Pichia pastoris for protein expression. Consequences showed that the enzyme created by lac I had a good solvent/salt tolerance, demonstrating that it might be used in a variety of biotechnological applications [64]. Jin et al [65] stated the identification of the lac I gene from Ganoderma tsugae, which was found to have the ligninolytic capacity in knockout tests.…”
Section: Lignin Depolymerization From Enzymes Produced By Fungimentioning
confidence: 99%